Pengembangan Sanggar Animasi GMC sebagai Youth Creative Media Industry di Surakarta dengan Pendekatan Arsitektur Kontemporer - Anggelia Wulandari, Widya; , Dr. Ir. Qomarun, MM; , Ms.Priyono Nugroho, ST, MT (2016)
Today many animation studio in the middle of the animation industry in Indonesia, especially in Surakarta. One of them namely is GMC Animation Studio or better known as the GMC Animation which a place or means used by a community or group of people to do an activity that is the process of displaying objects so that the image will appear live. On 20 September 2013 in Jakarta, Solo was named the National Creative City. This coronation is not out of Solo's Youth Creativity, because the young people typically have high creativity. Therefore, this animation studio will be developed to creative media industry (print and audio-visual media) to accommodate Solo's youth creativity. Creative industry need of human resources of high quality through the notion or innovative idea. So, necessary development of GMC's Animation Studio as Youth Creative Media Industry in Surakarta with Contemporary Architecture approach. The goal is to accommodate youth creativity in the media sector to do an activity such as training, learning, creation and production in Surakarta in media sector. Keywords: Animation, Creative Industry, Media Industry